Analisis Deskriptif Pembelajaran Dasar Listrik Elektronika selama Pandemi Covid-19 - Fischa Prima Eka putri; Hansi Effendi (Jurnal Pendidikan Teknik Elektro, 2023)
This article reviews the implementation of online learning and student motivation during a pandemic in the basic subjects of electricity and electronics at SMK Negeri 5 Padang. This research answers the question of how to describe the implementation of online learning and students' learning motivation in the Basic Electricity and Electronics (DLE) subject at SMK 5 Padang. This research is a quantitative study with a population of all students of class X who take Basic Electricity and Electronics (DLE) subjects at SMK 5 Padang City with a total of 35 people. The results showed that the learning constraints in the category of students who chose Yes showed a percentage of 61.4%. The category that chose Not showed a percentage of 38.6%. Regarding online learning resources, students who chose Yes showed a percentage of 40.7%. The category that chose Not showed a percentage of 59.3%. There is a desire and desire of students to learn who choose Yes shows a percentage of 90%. The category that chose No shows a percentage of 10%. There is encouragement and need for students in learning who choose Yes to show a percentage of 45.7%. The category that chose Not showed a percentage of 54.3%. There is hope that students in the future who choose Yes show a percentage of 79.4%. The category that chose No shows a percentage of 20.6%.